Pengaruh Kualitas Layanan Pelaku Wisata Terhadap Tingkat Kepuasan Wisatawan Mancanegara Di Taman Nasional Tanjung Puting, Kabupaten Kotawaringin Barat - Koentarto, Ilham; Hasaruddin, Hasaruddin (Universitas Indo Global Mandiri Palembang, 2021)
Indonesian tourism in 2019 provided the second largest contribution after CPO in providing foreign exchange. With this development, currently various regions in Indonesia are developing tourism, one of which is in West Kotawangin Regency with the Tanjung Puting National Plant (TNTP) destination. To develop regional tourism, extra services are needed by tourism actors such as guides, Klotok, food and so on in order to provide satisfaction for both foreign tourists (tourists) and domestic tourists (Wisnus). Therefore, this study aims to 1) determine the effect of the quality of tour kelotok services, on the satisfaction level of foreign tourists visiting Tanjung Puting National Park. 2) Knowing the effect of the quality of tour guide services on the level of satisfaction of foreign tourists visiting Tanjung Puting National Park. 3) Knowing the effect of the quality of food and baverage services on the level of satisfaction of foreign tourists visiting the Tanjung Put National Park. and 4) Knowing the effect of hotel service quality on the level of satisfaction of foreign tourists visiting Tanjung Puting National Park. The research method used. in this research is quantitative with data analysis using Multiple Linear Regression Analysis. The results of the study show that the service quality of tourist services has an effect on the level of satisfaction of foreign tourists, both tour group services, guide services, food and baverage services and hotel services as a whole (simultaneously) have an effect of 60.1% on the level satisfaction of foreign tourists.